Penggunaan Model Jigsaw dalam Meningkatkan Pemahaman Siswa Kelas 9.3 pada Pelajaran IPS Materi Sejarah di SMPN 16 Bogor - Gunarti Sukriyatun (Universitas Negeri Yogyakarta, 2017)
AbstractThe purpose of this research is to know the improvement of quality learning process and learning outcomes of Social Sciences in class 9.3 through model of cooperative Learning Jigsaw. The population of this research is the class 9.3 SMP N 16 Bogor of elementary students are consisted 38 students, there are 23 female and 15 male students. The result of this research showed in the first cycle get the value 71,32 or completeness study of 50,00% while in the second cycle get the value 77,63 or completeness study of 71,05%, it means that the research is successfully. Meanwhile, the assessment of quality in learning on the first cycle is 86,67% and the second cycle is 98,33%. In the other hand, the observation result of students behavior are showed an increasing with the value of the first cycle is 57,89% and in the second cycle is get the value 70,17%. Based on the result of this research above, it can be conclude that the implementation of Jigsaw by Cooperative Model can improve the result in cognitive learning of Social Sciences. In addition it can improve the quality of learning and participation with students’ behavior. Keywords: Results of learning, Cooperative Learning Model Jigsaw